Mecanismos de proteção ao acionista e ao credor e política de dividendos: uma análise internacional dos modelos de resultado e de substituição - Rodrigues, Ana Cristina Miranda (2019)
This thesis investigates the effects of investor protection mechanisms on corporate dividend policies, extending the analysis of outcome model and substitute model to the creditor. To support the hypotheses formulated, complementary steps are developed, including summary statistics; median equality tests; panel data regressions, under fixed effects; regressions Tobit and Logit; robustness tests, which include the Two-Stage Least Squares (2SLS) estimates and the Generalized Momentary Method (GMM). The empirical results are based on data from 18,607 companies in 40 countries from 2008 to 2017. The results of the econometric models used, with industry-adjusted data, explanatory variable lags and endogeneity tests confirm Hypotheses H1 and H3 of this thesis, showing the negative relations between shareholder protection, investment opportunity and dividend payment. That is, firms located in countries with high shareholder protection and better investment opportunities are less likely to pay dividends, as they do, indicating greater effectiveness of the result and substitution models, from the shareholder's perspective. However, from the perspective of the lender, relations negative and significant variables related to the right of the creditor and debt in all the models used in this thesis, allow us to infer that in high protection condition, the lender restricts payment and, conversely, when under-protection, companies pay more dividends. These results are inconsistent with the outcome and substitution models from the lender's perspective and do not support Hypotheses H2 and H4 of this thesis. An alternative explanation for this scenario may be related to the need to guarantee the company's reputation with the capital market. That is, due to credit market weakness and the low level of creditor protection, possibly, managers are forced to maintain good relationships with the capital market paying more dividends. Conversely, in the case of high shareholder protection, the propensity to pay dividends, such as the payment itself, is lower. The results of this thesis reinforce La Porta, Lopes-de-Sinales, Shleifer and Vishny (2000), but are inconsistent with Brockman e Unlu (2009), Byrne and O’Connor (2012 and Shao, Kwok and Guedhami (2013), as they do not present evidence of dividend increases when increased creditor protection combined with new investment opportunities. Moreover, it is not possible to realize that dividend payments are more sensitive to creditor rights compared to shareholder rights, but both have equally significant negative effects on dividend distribution. This situation suggests that shareholders' rights are more determinant in the dividend substitution and result models. Within this context, and s ta thesis contributes to the Theory of Dividends Agency, as noted, from these results, the effects of the debt protection mechanisms on institutional policy dividends are not consistent with the models income and substitution of dividends, and provide empirical evidence of negative relationships of protection mechanisms to the creditor on the decisions of corporate dividends. The first approach of this thesis, related to the effects of investment opportunities on dividend policy, based on shareholder rights, broadens the analyzes of La Porta et al. (2000). The second, additional and higher-contribution approach concerns the analysis of the effect of creditor protection on dividends, the results of which, using the result and substitution agency models, do not confirm that in countries with high credit protection, firms with good investment opportunities pay more dividends, nor do they confirm that firms with good investment opportunities, located in countries with low debt protection, pay less dividends. Within this context, it is possible to affirm that the shareholder right is more determinant to explain the dividend policies, according to the result and substitution agency models.